Polish Independent Press Summary, no. 17 (1988) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
A digest of Polish underground press (including articles, tables of content, and book covers) compiled by members of the RFE Polish Underground Publications Unit to be used in a daily 20-minute broadcast on Polish samizdat. Extract from Tygodnik Mazowsze, no. 234 (13 January 1988). Extract from Przegląd Wiadmości Agencyjnych, no. 2(129) (13 January 1988). Table of Contents from Kultura Niezależna, no. 35 (November 1987). Extract from Kultura Niezależna, no. 35 (November 1987). Table of Contents from Kultura Niezależna, no. 36 (December 1987). Extract from Kultura Niezależna, no. 36 (December 1987). Table of Contents from Almanach Humanistyczny, no. 7 (1987). Extract from Almanach Humanistyczny, no. 7 (1987). Table of Contents from Krytyka, no. 26 (1987).